PERANCANGAN ALAT UKUR KANDUNGAN GAS CO PADA GAS BUANG KENDARAAN BERMOTOR MENGGUNAKAN SENSOR MQ-7 BERBASIS MIKROKONTROLER AT89S52 - Didi Jimbarwan, I Gede; Supardi, I Wayan; Wendri, Nyoman (BULETIN FISIKA; Vol 14 No 2 (2013): BULETIN FISIKA, 2013)
It has designed and developed a measurement tools CO gas in emissien gas of motor vehicle using MQ-7 based of AT89S52 microcontroller. The system AT89S52 microcontroller as the main processor, LM 741 as a voltage amplifier, ADC 0804 as the voltage converter into digital data, LCD as a display, and using basic language as a software. From the measurement using ten motorcycles obtainable R 2 values 0,983 ?? between the tool and the reference.